White matter microstructure of the neural emotion regulation circuitry in mild traumatic brain injury - Horn, Harm Jan; Mangina, Namrata R.; Rakers, Sandra E.; Kok, Jelmer G.; Timmerman, Marieke E.; Leemans, Alexander; Spikman, Jacoba M.; Naalt, Joukje (The European journal of neuroscience, 2021)
Emotion regulation is related to recovery after mild traumatic brain injury (mTBI). This longitudinal tractography study examined white matter tracts subserving emotion regulation across the spectrum of mTBI, with a focus on persistent symptoms. Four groups were examined: (a) symptomatic (n = 33) and (b) asymptomatic (n = 20) patients with uncomplicated mTBI (i.e., no lesions on computed tomography [CT]), (c) patients with CT‐lesions in the frontal areas (n = 14), and (d) healthy controls (HC) (n = 20). Diffusion and conventional MRI were performed approximately 1‐ and 3‐months post‐injury. Whole‐brain deterministic tractography followed by region of interest analyses was used to identify forceps minor (FM), uncinate fasciculus (UF), and cingulum bundle as tracts of interest. An adjusted version of the ExploreDTI Atlas Based Tractography method was used to obtain reliable tracts for every subject. Mean fractional anisotropy (FA), mean, radial and axial diffusivity (MD, RD, AD), and number of streamlines were studied per tract. Linear mixed models showed lower FA, and higher MD, and RD of the right UF in asymptomatic patients with uncomplicated mTBI relative to symptomatic patients and HC. Diffusion alterations were most pronounced in the group with frontal lesions on CT, particularly in the FM and UF; these effects increased over time. Within the group of patients with uncomplicated mTBI, there were no associations of diffusion measures with the number of symptoms nor with lesions on conventional MRI. In conclusion, mTBI can cause microstructural changes in emotion regulation tracts, however, no explanation was found for the presence of symptoms. This diffusion MRI study examined frontal tracts supporting emotion regulation in patients with mild traumatic brain injury (mTBI). Asymptomatic patients with uncomplicated (i.e., no lesions on computed tomography [CT]) mTBI showed changes in the microstructure of the right uncinate fasciculus (UF), whereas symptomatic patients did not. Microstructural changes were most pronounced in patients with frontal lesions on CT, particularly in the forceps minor and UF. In uncomplicated mTBI, tract microstructure was not related to the number of symptoms or lesions on conventional MRI.